Betalain–Chickpea Protein Particles Produced by Freeze Drying and Spray Drying: Physicochemical Aspects, Storage Stability, and In Vitro Digestion - Mary H. Grace; Roberta Targino Hoskin; Malak Alghamdi; Mary Ann Lila; Vesela I. Chalova (Foods)
Beetroots are one of the primary sources of betalains, nitrogenous pigments with anti-inflammatory and antioxidant properties. However, due to their chemical instability, betalains have limited use in food applications. This work investigated whether betalains encapsulated in chickpea protein could be stabilized and delivered in a shelf-stable format. Freeze-dried (CB-FD) and spray-dried (CB-SD) protein–betalain particles encapsulated in chickpea protein isolate (6% w/v) were prepared. The encapsulation method affected particles’ morphology, water activity, hygroscopicity, solubility, and color. Particles captured total betalains of 9.30 ± 0.61 and 4.40 ± 0.92 mg/g for CB-SD and CB-FD, respectively. LC-MS identified 12 betacyanins and 6 betaxanthins. The stability of betalains revealed that encapsulation efficiently preserved betalain integrity of over 6 weeks of storage at 4, 22, and 40 °C compared to dry beetroot extract. CB-SD particles were stable with no significant changes, while CB-FD showed slight degradation after 4 weeks due to increased Aw. Antioxidant activity correlated well with betalain concentration. In vitro digestion resulted in only 25% bioaccessibility of betacyanins, while betaxanthins were more stable with 100% recovery. Encapsulation with chickpea protein isolate is an efficient and straightforward strategy for expanding and diversifying applications of phytochemical-rich beetroot extracts for the food industry.